Análise estrutural numérica de rolos poliméricos de esteiras transportadoras de minérios - Sumida, Fábio Satoshi (2023)
The use of conveyor belts systems is of great importance, particularly in mining industry, where these belts are used to transport bulk ore, frequently to great distances. The rollers have fundamental function on those systems directing and supporting the conveyor belt and the transported material weight. Designing these systems inadequately can lead to unnecessary expenses on oversizing and maintenance, as well as increase in the risk of physical damage to those involved. An alternative to conventional rollers (metal made) is polymer rollers, which are the focus of this paper. The project’s goal is to perform simulations using the finite element method to analyse the structural behaviour of those rollers, identifying possible improvements and failure points. For this purpose, four different geometries of commercial polymer rollers were analysed, using different materials described in the literature and commercially available, such as polyamide, polypropylene, and high-density polyethylene. Throughout this paper, the materials used, the contact regions between the rollers, the belt, and the support, the boundary conditions applied in the simulations, as well as the equations, approximations, and considerations used were detailed. The evaluation criteria used were: the maximum von Mises stress, the deflection angle in the bearings and also the maximal vertical deflection of the shaft and tube. The first two criteria are based on ABNT NBR 6678:2017 standard. After performing the analyses in the four rollers, it was concluded that one of them needs adjustments and/or modifications, while the other three were approved in the evaluated criteria for the manufacturer’s geometry and material. Among these three, it was identified that two of them could be optimized.